The constitutive equation gap method - Syed Muhammad, Kashif (International Islamic University Malaysia Press, 2011)
This chapter discusses constitutive equation gap method used for identification of materials constitutive parameters. It involves a comparison of given stress field and displacement field to a computed stress field generated by using an initial set of materials constitutive model. This method is based on the gap estimation and minimization that is measured as the distance between the two stress fields using a particular constitutive model. The method is found to be applicable and has shown promising results with the use of full field data used for material characterization.